Genetic diversity of saltwater crocodiles (Crocodylus porosus) from Sarawak using microsatellite approach - Nor Yasmin, Kasim (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Crocodylus porosus (saltwater crocodile) locally known as Bujang Senang is the common crocodile found in Sarawak. There were several genetic studies related to C. porosus in Sarawak that have been conducted, however relationships between C. porosus in Sarawak remained unresolved. Therefore, this study is aimed to assess genetic diversity of C. porosus obtained from different locations in Sarawak using microsatellite approach. Available C. porosus tissues samples were subjected to total genomic DNA extraction using modified CTAB method, Polymerase Chain Reaction – Simple Sequence Repeats (PCR-SSRs) and data analysis. Microsatellite loci for C. porosus from Sibu, Miri and Bako of approximately 115 to 122 base pairs (bp) were successfully obtained during this study. C. porosus from Sibu showed repeat motifs of (GT)22 (GA)5, Miri (GT)21 (GA)5 and Bako (GT)20 (GA)5. Phylogenetic tree construction using Unweighted Pair Group with Arithmetic Averages (UPGMA) and Maximum Parsimony (MP) methods revealed monophyletic grouping of C. porosus.